2009
DOI: 10.1097/rti.0b013e318191987e
|View full text |Cite
|
Sign up to set email alerts
|

Psittacosis Presenting as a Halo Sign on High-resolution Computed Tomography

Abstract: Psittacosis is an infectious disease caused by the intracellular microorganism Chlamydia psittaci, which mainly affects the respiratory tract. We described the high-resolution computed tomography findings in a 30-year-old man with psittacosis acquired by contact with psittacides. The diagnosis was confirmed by serological methods. High-resolution computed tomography showed nodular opacities surrounded by ground-glass attenuation (halo sign) in both lower lobes. Psittacosis should be considered in the different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…Besides, lesions could occur in any lobe, mainly in the inferior lobe and unilateral lung, particularly the right lung, and hilar lymphadenectasis was uncommon. [19][20][21][22] Broadly consistent but slightly different, lesions tended to occur in the left lung inferior lobe in our study, which may be related to small sample size. In addition, we also found that the early-stage lesions were small in scope and more common in the subpleura.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Besides, lesions could occur in any lobe, mainly in the inferior lobe and unilateral lung, particularly the right lung, and hilar lymphadenectasis was uncommon. [19][20][21][22] Broadly consistent but slightly different, lesions tended to occur in the left lung inferior lobe in our study, which may be related to small sample size. In addition, we also found that the early-stage lesions were small in scope and more common in the subpleura.…”
Section: Discussionsupporting
confidence: 50%
“…Studies have shown that the radiographic features of C. psittaci pneumonia were mainly patchy consolidation shadows or ground‐glass density shadows, bronchiectasis, involvement in one or both lungs, inflammatory effusion of one or more lobes and partial pleural effusion. Besides, lesions could occur in any lobe, mainly in the inferior lobe and unilateral lung, particularly the right lung, and hilar lymphadenectasis was uncommon 19–22 . Broadly consistent but slightly different, lesions tended to occur in the left lung inferior lobe in our study, which may be related to small sample size.…”
Section: Discussionsupporting
confidence: 40%
“…In these cases, only two patients had normal chest imaging. High-resolution CT shows that some lesion areas are solid nodular and ground glass [22]. Among the two cases we have reported, there were solid or ground glass pulmonary shadows, and hilar lymphadenopathy and pleural effusion in case 2.…”
Section: Discussionmentioning
confidence: 75%
“… 9 , 27 , 28 Seventy percent of these patients have pleural effusion manifestations, which are directly proportional to the severity of the disease, and severe pneumonia may present with bilateral pleural effusion. Hochhegger et al 29 proposed that chest CT in psittacine pneumonia can present as nodular shadows in both lower lungs or peripheral halo signs, but imaging diagnosis always lacks specificity. It can be combined with medical history, laboratory tests, and clinical manifestations, but the final diagnosis depends on etiology.…”
Section: Diagnostic Techniquesmentioning
confidence: 99%